ANALYSIS OF STUDENT’S LEARNING DIFFICULTIES IN THE IMPLEMENTATION OF SCIENCE PRACTICUM AT SMP NEGERI 2 MARBAU - Chey, Salwa Cheylani Lukito; Novi Fitriandika Sari; Ika Chastanti (International Journal of Cultural and Social Science, 2025)
This study aims to analyze the learning difficulties of VIII grade students of SMP Negeri 2 Marbau in the implementation of science practicum. The learning difficulties studied include four main indicators, namely infrastructure facilities, practicum implementation process, technical constraints, and mastery of theory. The research method used was descriptive qualitative with total sampling technique as many as 167 students as respondents. Data were obtained through questionnaires, interviews, and documentation, then analyzed using a percentage approach. The results showed that the highest difficulty lies in the aspect of infrastructure facilities with a very high category (82.25%), followed by the practicum implementation process (78.8%) and technical constraints (75.5%) which are included in the high category. Meanwhile, mastery of theory was classified as low in difficulty (36.6%), indicating an imbalance between students' conceptual understanding and practicum skills. These findings indicate the need for improvements in the provision of laboratory facilities, training in science process skills, and the design of more authentic practicum activities to improve students' overall scientific competence.